An Improved Model of Internet Pricing Scheme Of Multi Link Multi Service Network With Various Value of Base Price, Quality Premium and QoS Level - Fitri Maya Puspita (ICON-CSE, 2014)
Internet Service Providers (ISPs) nowadays deal with high demand to promote good quality information. However, the knowledge to develop new pricing scheme that serve both customers and supplier is known, but only a few pricing plans involve QoS networks. This study will seek new proposed pricing plans offered under multi link multi service networks. The multi link multi service networks scheme is solved as an optimization model by comparing our four cases set up to achieve ISPs goals in obtaining profit. The decisions whether to set up base price to be fixed to recover the cost or to be varied to compete in the market are considered. Also, the options of quality premium to be fixed to enable user to choose classes according to their preferences and budget or to be varied to enable ISP to promote certain service are set up. Finally, we compare the previous research with our model to obtain better result in maximizing the ISPs profit.